Vertical versus Horizontal Tax Incentives Policies in Brazil: Assessing the Impacts Using a Computable General Equilibrium Model - Alexandre Porsse; Felipe Madruga (European Regional Science Association (ERSA), 2015)
Since the 2009 financial crisis, some national governments have adopted anticyclical tax policies for recovering and economic growth. These policies can be different in terms of what type of tax incentive policy (income, labor, value added) is chosen as well if the strategy is vertical, benefiting some sectors, or horizontal, benefiting all economic sectors. In Brazil, one of the anticyclical tax policy carried out by the federal government was to reduce the value added tax named ?Imposto sobre Produtos Industrializados? (IPI) using a vertical strategy mainly benefiting the automobile sector among few others. Taking into account this recent experience, this paper aims primary to assess the efficacy of vertical versus horizontal tax incentive policies for promoting economic recovering. Additionally, the paper addresses the distributive effects of these policy strategies considering the impact on the income classes as well on the regional public finances. Considering the price effects of tax policies, the computable general equilibrium approach is the most appropriated methodological framework to achieve the objectives of this paper. We calibrated a CGE model for the Brazilian economy for 2007, recognizing the productive structure for 56 sectors and 8 types of labor segmented by income classes. This model is integrated with a public finance module specifying the government accounts for each level of government (federal, states and municipalities) as well the vertical fiscal linkages. The CGE model allow short run and long run simulations. The CGE model was used for simulating two shock scenarios. The first one represents the vertical tax policy and simulate a reduction in the IPI tax rate of the automobile sector in accordance with the average incentives over the period 2010-2013. The second one represents the horizontal tax policy and the simulation imply reductions in the IPI tax rate of all sector keeping the amount of tax revenue reduction equal to the vertical shock. These shocks were simulated for a short run closure considering the transitory nature of anticyclical policies. The simulation results show that the economic impact of vertical and horizontal tax incentives strategies are quite similar. The policy implication is that both strategies are indifferent in terms of the impact on GDP and employment. Nevertheless, the distributive impact evaluated through the effects on labor factor by income classes shows the vertical policy is more regressive than the horizontal policy. Considering the impact on the regional public finance, both policies imply reductions in the level of transfers to the regional governments due the vertical fiscal linkages of the Brazilian federalism. Despite the positive economic impact on GDP and employment, the magnitude of this effect is not so high and fiscal linkages among governments seems play an important role at least for the Brazilian economy.
Keywords: H23; H25; H30; 330; tax incentives; economic and distributive impacts; CGE model